Implementation Of the Iqra' Method in Learning to Read The Al-Qur'an In Early Age Children - Zahraturraihana, Zahraturraihana; Juwita, Intan; Yofinda, Vanesa; Neisha, Fella Hanna (Sekolah Tinggi Agama Islam Pengembangan Ilmu Al-Qur`an Sumatera Barat, 2024)
The first lesson given to children in Islamic education is learning about the Koran. By introducing the Qur'an from an early age, Qur'anic values will be ingrained and make people with character. This research aims to determine the implementation of the Iqra' method in learning to read the Koran in early childhood. This research uses descriptive qualitative methods to obtain broad and in-depth information related to the research objectives. The data sources in this research were the principal, class teachers, students and parents of the students at Sabbihisma 2 Padang Kindergarten. The research results show that the Iqra' method learning planning is not explained in detail in the form of a lesson plan. The teacher teaches it according to the teaching instructions in the Iqra' book. The Iqra' method learning is carried out privately, students are called one by one to come forward to read Iqra'. Students are required to be active in reading, while the teacher guides and directs the learning process. Evaluation of Iqra' method learning is carried out during Iqra' learning by the teacher and EBTA at the end of each volume of Iqra' is carried out by the school principal. Supporting factors for learning Iqra' are providing motivation to students, the role of parents who support learning Iqra' or the Koran at home, conveying the Iqra' method to parents of students, and teacher training. Meanwhile, the inhibiting factors are students' low memory capacity, students who are unable to concentrate, and lack of repetition of Iqra' or Al-Qur'an reading at home.